Antiproliferative Effects and Apoptosis induction of Ethanolic Extract of Andrachna aspera on Human Rabdomyosarcoma Cells - Hidayat, Hazha J. (Iraqi Journal of Cancer and Medical Genetics, 2015)
Arial part of Andrachna aspera ethanolic extract was evaluated by studying their effect on human rabdomyosarcoma (RD) cell line. The cytotoxic activity was determined by anti-proliferative effects when the human rabdomyosarcoma cells were cultured under different concentrations. After 24, 48 and 72h when treated with the ethanolic extract, using cell viability assay. The plant extract showed the strong cytotoxic affect upon the cell like RD with IC50 of 25 µg/ml concentration after 72h, Furthermore, cell cycle analysis showed a significant increase in the accumulation of RD- treated cells at G0/G1 phase (p<0.01), and apoptotic rate also shows significantly increasing in a dose- time dependent manner.The extract of A. aspera induced apoptosis and possessed the most robust anticancer activity, against RD cells